Landasan Filosofis Integrasi Ilmu Pengetahuan dan Agama: The Philosophical Bases for Integration of Science and Religion - Rahma, Anisa Alya; Afifah, Afifah; Muniron, Muniron (University of Darussalam Gontor, Indonesia, 2024)
This article aims to examine and formulate a model for integrating religious knowledge with general science, focusing on the ontological, epistemological, and axiological foundations. In the context of modern secularism, which has led to the separation of religion and scientific knowledge, this research seeks to restore spiritual values within scientific inquiry and integrate the two disciplines to create knowledge that is not value-free. The research method used by the author is a qualitative approach with a type of library research with data collection methods by conducting documentation studies by examining primary and secondary sources in the form of books and scientific articles. The results of this study concluded that the integration of science is an effort to combine religious science and general science by incorporating religious values into it and looking for similarities between the two. Integration is done to make science not free of moral values and create good human beings who are in accordance with the two functions of human creation, namely as khalifah and good servants of Allah. The philosophical bases of science integration include ontological, epistemological and axiological bases. From the ontological basis, the relationship between the highest reality, namely God, and the lowest reality, namely creatures, has a close and inseparable relationship. Epistemologically, the source of general and religious knowledge comes from one source, namely God, who then provides means or tools of knowledge in the form of reason and the five senses, as a tool for obtaining knowledge and Islamic epistemology recognizes the means of knowledge in the form of intuition to achieve metaphysical-immaterial knowledge, where this method of intuition is in the form of inspiration and revelation. And axiologically, the integration of general science and religious science gives birth to science that is not value-free, so that it can make the development of science consistent with moral values in accordance with religion and the Qur'an, which gives birth to benefits in the world and the hereafter in the form of material, intellectual and spiritual enjoyment in humans who are a unity between body and spirit.